AN ECONOMIC ANALYSIS OF SERICULTURE IN THE REPUBLIC OF UZBEKISTAN AND DEVELOPMENT OF ITS COMPETITIVENESS (Journal of Pharmaceutical Negative Results, 2022)
Economic potentials of Sericulture and its popularity are reflected by the fact that it is no longer limited to the traditional areas of sericulture. Sericulture provides much needed employment, income and foreign exchange in developing and labour rich countries, especially Uzbekistan. Knowing these things, current article was stated to highlight the growth and instability in silk production in Uzbekistan. Studied geographic export map in raw silk in the world. When Uzbekistan had become the independence, silk industry carried out structural reforms that aimed further deepening economic reforms in this the field. Therefore, creating favorable conditions for attracting foreign investment in silk industry, to modernize and create new fabrics, increase the volume and expand the range of finished products that are competitive in the world the market.